Pendidikan Islam dan Pengembangan Kesadaran Lingkungan - Nurulloh, Endang Syarif (Jurnal Penelitian Pendidikan Islam, 2019)
Development of awareness of the importance of the environment is a journey that must be pioneered for the sake of the survival of the next generation so that it is not threatened due to irresponsible human behavior today. Environmental education aims at introducing various values ​​and explaining concepts to develop the ability of attitudes and skills needed to understand and appreciate the mutual relations between humans, culture, and the biophysical environment. This analysis was developed as an effort to further explore the development of environmental awareness in Islamic education. The development of environmental awareness can be implemented through religious values ​​with an environmental perspective in Islamic educational institutions. The religious climate in the environment in Islamic educational institutions can be realized through approaches: 1) the creation of a religious education environment, 2) the realization of worship facilities, 3) the realization of the learning method by using the approach of religious values ​​in every learning, especially religious values ​​with an environmental perspective 4 ) the realization of the example of educators who have noble morals in particular having a concern for the environment.